(untitled) (MAUSAM, 2020)
Precipitable water vapour (PWV) plays a key role in the atmospheric processes from climate change to micrometeorology. Its distribution and quantity are critical for the description of state and evaluation of the atmosphere in NWP model. Lack of precise and continuous water vapour data is one of the major error sources in short term forecast of precipitation. The task of accurately measuring atmospheric water vapour is challenging. Conventional in situ measurements of atmospheric water vapour is provided by GPS Sonde humidity sensors profile twice a day at 0000 and 1200 UTC mainly from limited land regions. In recent years India Meteorological Department (IMD) is computing PWV from 19 channel sounder of INSAT-3D in three layers 1000-900 hPa, 900-700 hPa and 700-300 hPa and total PWV in the vertical column of atmosphere stretching from surface to about 100 hPa under cloud free condition. These data most commonly were validated using spatially and temporally collocated GPS Sonde measurements. In this paper, INSAT-3D satellite retrieved PWV data are validated with column integrated PWV estimates from a network of ground based Global Navigation Satellite System (GNSS) over Indian subcontinent. The PWV retrieved by INSAT-3D sounder platform is very promising, being in a good agreement with the GNSS data recorded over India for the period June, 2017 to May, 2018. The root-mean-square (rms) differences of 5.4 to 7.1 mm, bias of -4.7 to +2.1 mm and correlations coefficient of 0.79 to 0.92 was observed between INSAT-3D and GNSS PWV. The correlations coefficient between GPS Sonde and GNSS derived PWV ranges from 0.85 to 0.98.